Structures of L-BC virus and its open particle provide insight into Totivirus capsid assembly - Grybchuk, Danyil; Procházková, Michaela; Füzik, Tibor; Konovalovas, Aleksandras; Serva, Saulius; Yurchenko, Vyacheslav; Plevka, Pavel (Communications biology, 2022)
L-BC virus persists in the budding yeast Saccharomyces cerevisiae, whereas other viruses from the family Totiviridae infect a diverse group of organisms including protists, fungi, arthropods, and vertebrates. The presence of totiviruses alters the fitness of the host organisms, for example, by maintaining the killer system in yeast or increasing the virulence of Leishmania guyanensis. Despite the importance of totiviruses for their host survival, there is limited information about Totivirus structure and assembly. Here we used cryo-electron microscopy to determine the structure of L-BC virus to a resolution of 2.9 Å. The L-BC capsid is organized with icosahedral symmetry, with each asymmetric unit composed of two copies of the capsid protein. Decamers of capsid proteins are stabilized by domain swapping of the C-termini of subunits located around icosahedral fivefold axes. We show that capsids of 9% of particles in a purified L-BC sample were open and lacked one decamer of capsid proteins. The existence of the open particles together with domain swapping within a decamer provides evidence that Totiviridae capsids assemble from the decamers of capsid proteins. Furthermore, the open particles may be assembly intermediates that are prepared for the incorporation of the virus (+) strand RNA.
Keywords: virové plášťové proteiny; viry; Animals; Totivirus; elektronová kryomikroskopie; kapsida; Capsid Proteins; zvířata; Viruses; Cryoelectron Microscopy; Capsid